2004
DOI: 10.1097/01.wnr.0000137183.68847.4e
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment improves cognition in aged Alzheimer's transgenic mice despite stable β-amyloid deposition

Abstract: Environmental enrichment (EE) has been shown to improve cognitive performance and brain indices of cognition in normal mice and rats. Because the therapeutic potential of intensive, long-term EE to benefit patients with Alzheimer's disease (AD) has yet to be explored, the present study evaluated the effect of long-term EE on cognition in an animal model of AD, the APPsw transgenic mouse. Beginning at 16 months of age, APPsw mice were put into EE or standard housing for 4 months and then tested in four cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
2
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(157 citation statements)
references
References 15 publications
10
138
2
7
Order By: Relevance
“…This supports the notion that novel experiences stimulate processes of neural plasticity mediated by gene expression that in turn enhances cognitive processing (Rampon et al 2000) even in older age (Swaab and Bao 2011). The association between experience and neural plasticity has been repeatedly reported both in animal and human studies (Arendash et al 2004;Bhardwaj et al 2006;Curtis et al 2007;Eriksson et al 1998;Frick and Fernandez 2003;Kempermann et al 1997;Milgram et al 2006). New experiences or managing of complex situations are a form of learning which are accompanied by synaptic plasticity (Whitlock et al 2006) and neurogenesis (Pereira et al 2007).…”
Section: Neuronal Plasticity and Compensation In Agingsupporting
confidence: 54%
“…This supports the notion that novel experiences stimulate processes of neural plasticity mediated by gene expression that in turn enhances cognitive processing (Rampon et al 2000) even in older age (Swaab and Bao 2011). The association between experience and neural plasticity has been repeatedly reported both in animal and human studies (Arendash et al 2004;Bhardwaj et al 2006;Curtis et al 2007;Eriksson et al 1998;Frick and Fernandez 2003;Kempermann et al 1997;Milgram et al 2006). New experiences or managing of complex situations are a form of learning which are accompanied by synaptic plasticity (Whitlock et al 2006) and neurogenesis (Pereira et al 2007).…”
Section: Neuronal Plasticity and Compensation In Agingsupporting
confidence: 54%
“…Jankowsky et al 182,188 unexpectedly reported that EE APP/ PS1 transgenic mice develop a higher amyloid burden with increases in aggregated and total Ab levels, particularly in the hippocampus. Arendash et al 184 failed to observe any change in Ab deposition in EE APP transgenic mice. In contrast, Lazarov et al 189 reported a decrease in hippocampal and cortical Ab levels and amyloid deposits in EE APP/PS1 transgenic animals compared with standard-housed controls.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Enriched mice transgenic for human APOE3 showed improved learning and memory associated with higher hippocampal levels of presynaptic protein synaptophysin and of NGF, whereas mice transgenic for human APOE4 were unaffected by EE. EE has repeatedly been reported to enhance performance in various cognitive tasks in transgenic mice carrying a double mutation at the level of both APP and PS1 genes, 182,183 in mice carrying the so-called Swedish mutation (SweAPP), [184][185][186] and in AD11 transgenic mice expressing a recombinant anti-NGF factor antibody. 187 The effect of EE on Ab levels and plaque deposition, as well as their impact on cognitive improvement, is controversial.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Both cognitive function improvements and decreases in neuropathology have been seen in mice that are exposed to an enriched environment at a young age; this is seen in PS1=DAPP mice (35), AD11 mice (14), and PS1 and PS2 KO mice (40). APPswe mice placed in EE at a later age (16 months) showed improvements in cognitive function compared with home cage controls, but without a decrease in Ab levels (10). Similar findings were reported for APP23 mice that started EE at 10 weeks of age and showed improved water maze performance but stable Ab levels (175).…”
Section: Animal Studiesmentioning
confidence: 98%